(untitled) (History Journal «Jerónimo Zurita», 2025)
Leonor Manrique de Sotomayor y Zúñiga took control of the House of Medina Sidonia after the death of the VI Duke, managing the estate and defending the legitimacy of her son. A patron of humanists, she promoted art and culture at court. She established strategic marital alliances and administered the economy of the duchy, as well as the exploitation of tuna traps, despite tensions with the Crown over the house’s privileges. In 1570, she relinquished her role as curator and became a beatified figure. Her trajectory highlights the influence and prominence of women in the Andalusian nobility of the 16th century.